Central bank communication with non-experts: A road to nowhere? - Michael Ehrmann; Alena Wabitsch (European Central Bank (ECB), 2021)
Central banks have intensified their communication with non-experts - an endeavour which some have argued is bound to fail. This paper studies English and German Twitter traffic about the ECB to understand whether its communication is received by non-experts and how it affects their views. It shows that Twitter traffic is responsive to ECB communication, also for non-experts. For several ECB communication events, Twitter constitutes primarily a channel to relay information: tweets become more factual and the views expressed more moderate and homogeneous. Other communication events, such as former President Draghi's "Whatever it takes" statement, trigger persistent traffic and a divergence in views. Also, ECB-related tweets are more likely to get retweeted or liked if they express stronger or more subjective views. Thus, Twitter also serves as a platform for controversial discussions. The findings suggest that central banks manage to reach non-experts, i.e. their communication is not a road to nowhere.
Keywords: E52; E58; 330; monetary policy; central bank communication; social media; non-experts